Lecturers’ Perceptions of Using Information, Communication and Technology (ICT) in Fkip Unilak - Herdi Herdi; Destina Kasriyati; Refika Andriani (Universitas Lancang Kuning, 2022)
Nowadays, ICT has huge potential to facilitate learning now, where online learning is as central media in education. Class activities directly is prohibited by government because spreading pandemic covid 19 in the world. This study aims at finding lecturers’ perceptions in using ICT as teaching and learning. This study used qualitative method. The data collection was done through a survey questionnaires consisting of open ended questions. The result of this research showed that the implementation ICT as learning media is effective. ICT helps teachers to be creative, it helps an easy in preparing the material for teaching. It can be concluded that ICT is very important to support teaching and learning process.